Pengaruh Penerapan Lembar Kerja Siswa Berbasis Inkuiri Terbimbing Terhadap Kemampuan Metakognisi Siswa Pada Materi Hukum II Newton - Ljianto Ljianto; Anita Anita; Boisandi Boisandi (Radiasi : Jurnal Berkala Pendidikan Fisika, 2020)
This study aims to determine; (1) students 'metacognition abilities before being applied to guided inquiry-based student worksheets on Newton's Law II material, (2) students' metacognition abilities after being applied guided inquiry-based student worksheets on Newton's Law II material, and (3) how much influence is the application of guided inquiry based student worksheets on students' metacognitive abilities in Newton's Law II material in class X Mia SMA N 1 Marau. This research is a pre-experimental research design with one group pretest-posttest design research. The population in this study were all students of class X SMA N 1 Marau which consisted of 4 classes. The sample selected using a saturated sample, namely class X Mia as the experimental class. The results of the study were obtained before the treatment of the aspects of students' high metacognition abilities, namely the aspect of strategy setting ability of 81.81% and the aspect of the lowest metacognition ability, namely the aspect of metacognition ability of the debugging strategy by 0%. Meanwhile, the results after being given treatment for the students' high metacognition ability were the aspect of strategic setting ability of 95.23% and the lowest aspect of metacognition ability was the aspect of the metacognition ability of the debugging strategy of 57.77%. The result of the calculation of the effect size is 5.17 or 5.17> 0.8. Thus, the effect of the application of guided inquiry-based worksheets is very influential on students' metacognition abilities.